Florida 4–H Horticulture Identification and Judging: Contest Rules and Glossary - Sydney Park Brown; Jeffrey G. Williamson; Tom Wichman (EDIS)
This publication provides guidelines and information for Florida 4H members and Master Gardeners interested in horticulture and/or in participating in state contests held annually at 4-H Congress or the Master Gardener Annual Conference.